1992
DOI: 10.1093/ptj/72.3.168
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Physical Therapy on Nursing Home Patient Outcomes

Abstract: The objective of this retrospective study was to assess the intensity and outcome of individual components of interdisciplinary care, including physical therapy, in a teaching nursing home. Two independent reviewers abstracted records from 90 consecutive patients admitted to the nursing home. They rated intensity and outcome of each program component using a structured, standardized data-abstraction form. Program components were physical therapy, speech therapy, psychosocial therapy, medication adjustment, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 8 publications
0
18
0
1
Order By: Relevance
“…A number of researchers studying different aspects of rehabilitation have demonstrated that a greater intensity of treatment results in better outcomes for the client compared with less intense treatment when other factors (e.g., diagnosis, age) are taken into account. For example, Chiodo, Gerety, Mulrow, Rhodes, and Tuley (1992) found that 88% of elderly nursing home residents who received highintensity physical therapy improved in physical function compared with 33% and 13% who received moderate and minimal intensity therapy, respectively. These changes could not be accounted for by age, cognitive status, level of independence in activities of daily living, or diagnoses.…”
mentioning
confidence: 99%
“…A number of researchers studying different aspects of rehabilitation have demonstrated that a greater intensity of treatment results in better outcomes for the client compared with less intense treatment when other factors (e.g., diagnosis, age) are taken into account. For example, Chiodo, Gerety, Mulrow, Rhodes, and Tuley (1992) found that 88% of elderly nursing home residents who received highintensity physical therapy improved in physical function compared with 33% and 13% who received moderate and minimal intensity therapy, respectively. These changes could not be accounted for by age, cognitive status, level of independence in activities of daily living, or diagnoses.…”
mentioning
confidence: 99%
“…Training programs that combine strength and balance training to improve mobility can significantly reduce the frequency of falls [5,8,22,33,35]. Programs of this kind have proved to have positive effects on the functional performance and psychological state of nursing home residents [9,44]. Likewise, physical training has also been shown to have beneficial effects on the strength, balance, reaction time, and flexibility of individuals with dementia [31].…”
Section: Improving Physical Performancementioning
confidence: 99%
“…1, 2 The rehabilitation of stroke survivor is a complex customized process planned for restoring the function of disabled to perform daily living activities and providing patient education, training and support for the stroke patient and the care giver family member(s). 3 The magnitude of stroke related disabilities are high. The current data supporting the effectiveness of rehabilitative interventions, time point for rehabilitation initiation are limited.…”
Section: Introductionmentioning
confidence: 99%